Consumers’ perception and experience in purchasing local fresh fruits from retail shops in Jasin, Melaka / Muhammad Hanif Ishak - Ishak, Muhammad Hanif (Faculty of Plantation and Agrotechnology, 2018)
This research explores the topic about consumers’ perception and experience in purchasing local fresh fruit from the retail shop in Jasin, Melaka. The main objective of this study was to investigate consumers’ perception and experience specifically describe the trend of purchasing, explore the key determinants choosing the favourable retail formats, and the definition of quality in purchasing fresh local fruits. The primary data was used in this study where the structured questionnaires were distributed to the target sample. This study included a target sample of 150 respondents, who were responsible for purchasing household produce. Stratified sampling and simple random sampling technique were used to get the sample of respondents during the study. The data was analyzed using Statistical Package for the Social Science (SPSS). The descriptive analysis was used and presented with frequency, correlation, cross tabulation while exploratory factor analysis used to measure pattern matrix, Kaiser-Meyer-Olkin, and Bartlett’s test of sphericity. The findings show that facilities, product presentation, condusive environment, structure, location, promotion, and services were the key determinant for the consumers in choosing their retail format in Jasin, Melaka. In addition, availability of various goods, price, and good services were the reason why consumers were choose modern retail format and quality attribute was the reason while choosing traditional retail format. In term of quality definition, credence attribute, variety, physical appearance, and extrinsic attribute were indicated the quality of local fresh fruits. Lastly, this study might found be as useful to people who were involved directly or indirectly in supply chain activities and soon will realize that these data very important in to guide them to achieve better acceleration in their marketing activities.